Use of CO2 in video assisted thoracic surgery and single-lumen endotracheal tube—a new less invasive approach - Gallego-Poveda, Javier; Guerra, Nuno Carvalho; Carvalheiro, Catarina; Ferreira, Hugo; Sena, André; Junqueira, Nádia; Velho, Tiago Rodrigues; Nobre, Ângelo (Journal of Thoracic Disease, 2017)
Carbon dioxide (CO2) has been extensively used to allow laparoscopic procedures, due to its extensive advantages in obtaining a fairly innocuous pneumoperitoneum to allow visceral dissection. Its use in video assisted thoracic surgery (VATS) has seldom been described. We present our experience in more than 100 patients, operated for various thoracic pathologies, in whom we created a surgical pneumothorax to allow different surgeries to be undertaken.